Imaging in Cardio-oncology: An Overview of an Emerging Medical Discipline. Issue 1 (January 2020) - Gilon, Dan; Leibowitz, David; Durst, Ronen; Iakobishvili, Zaza
Abstract : The world of cardio-oncology is an evolving field involving the assessment of cardiovascular disease in patients suffering from cancer. Cancer and cardiovascular diseases are the two leading causes of morbidity and mortality in the developed world. Globally, cancer is diagnosed in 12.7 million patients annually, and cancer incidence is projected to increase by 40% in high-income countries from 2008 to 2030. Chemotherapy is the main treatment for most cancers and improves survival, but is associated with significant cardiotoxicity. In recent years, the introduction of new biological anti-cancer treatments in addition to "classic" chemotherapy has further improved survival, but has also introduced new cardiovascular side effects beyond "pure" myocardial damage. The increasing number of patients with cancer and cancer survivors, and the growing complexity of cancer treatment and cardiovascular side effects, call for teamwork including cardiologists with specific training and expertise working in teams with oncologists, hematologists, and others. The purpose of this review was to describe the clinical background and importance of cardio-oncology, with an emphasis on the use of imaging in this clinical setting.